2019
DOI: 10.1214/19-ejp386
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate second order Poincaré inequalities for Poisson functionals

Abstract: Given a vector F = (F1, . . . , Fm) of Poisson functionals F1, . . . , Fm, we investigate the proximity between F and an m-dimensional centered Gaussian random vector NΣ with covariance matrix Σ ∈ R m×m . Apart from finding proximity bounds for the d2-and d3-distances, based on classes of smooth test functions, we obtain proximity bounds for the dconvex-distance, based on the less tractable test functions comprised of indicators of convex sets. The bounds for all three distances are shown to be of the same ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 32 publications
0
30
1
Order By: Relevance
“…Let f t = f h t be the solution of the Stein's equation ( 10) associated with h = h t . In [5] (see also [29]), it is shown that max…”
Section: Main Results: Bounds On the Convex Distancementioning
confidence: 99%
See 3 more Smart Citations
“…Let f t = f h t be the solution of the Stein's equation ( 10) associated with h = h t . In [5] (see also [29]), it is shown that max…”
Section: Main Results: Bounds On the Convex Distancementioning
confidence: 99%
“…As anticipated, to prove Theorem 1.2, we shall combine the somewhat classical smoothing estimate (14) with a remarkable bound by Schulte and Yukich [29].…”
Section: Main Results: Bounds On the Convex Distancementioning
confidence: 99%
See 2 more Smart Citations
“…15) which follows because the area of D α α α ∩ E is of order O(λ −1 ) and the intensity of Ξ is of order O(λ). Note that the bound (4.15) and all the upper bounds below are uniform in α α α and β β β.First, with (4.15) in mind, we obtainβ β β∈Dα α α∩E E{ς β β β | ς α α α = 1}ν(dβ β β) ≤ ν(D α α α ∩ E ) = O(1), β β β∈Dα α α∩E θ β β β ν(dβ β β) ≤ ν(D α α α ∩ E ) = O(1),which, together with (4.14), imply thatα α α∈E β β β∈Dα α α∩E {E(ς α α α ς β β β ) + θ α α α θ β β β }ν(dβ β β)ν(dα α α) = α α α∈E β β β∈Dα α α∩E {E [ς β β β | ς α α α = 1] + θ β β β } θ α α α ν(dβ β β)ν(dα α α) = O(1) α α α∈E θ α α α ν(α α α) = O(λ 1/2 ).…”
mentioning
confidence: 78%